Realistic simulation as a method of approaching patient safety with health professionals from the FSCMPA: experience report (Research, Society and Development, 2022)
Objective: To describe the experience of realistic simulation carried out with professionals from a reference hospital in maternal and child care in Pará. Method: This is a descriptive study of the experience report type, developed as part of the program alluding to the international month of patient safety to reinforce the training of the server of a public hospital that is a reference in maternal and child care in the North region. Results: The activity reached a total of 582 participants, 14.5% of whom were nurses, 44.5% nursing technicians, 13.7% practical arts agents, 15.4% were professionals from other areas of health, 8, 2% worked in administrative support and only 3.7% did not identify their professions. Conclusion: The results of this study show that there was an emphasis on the verbalization of the server's perception regarding the contributing factors of incidents related to care and the application of safety goals. Essay to contribute to the improvement of the research, learning and evaluation strategy of the target audience, to foster future studies and support health training within the realistic simulation.